THE EFFECT OF AMIL’S ISLAMIC CHARACTERISTICS ON THE QUALITY OF FINANCIAL REPORTING OF ZAKAT MANAGEMENT ORGANIZATIONS (ZMO): GOOD GOVERNANCE AS INTERVENING VARIABLE (International Journal of Islamic Business, 2022)
The objective of this research is to analyze the effect of Amil's Islamic Characteristics on Quality of Financial Reporting and Good Governance as an Intervening Variable in Zakat Management Organizations (ZMO). The research used the Structural Equation Modeling-Partial Least Square (SEM-PLS) method with SmartPLS software to analyze data from 204 samples of commissioners and administrators of Zakat Management Organization. The results show that the character of trustworthiness, professionalism, and good governance had a positive and significant effect on the quality of Financial Reporting. In contrast, Islamic religiosity has no impact on the quality of financial reporting. The results also show that Islamic religiosity, trustworthiness, and professionalism had a positive and significant effect on good governance. Good governance played a role in mediating the influence of trustworthiness on the quality of Financial Reporting. The research findings provide managerial implications for ZMO and the government to utilize Islamic religiosity and character of trustworthiness as qualitative standards in Amil recruitment. Furthermore, it allows them to create and set Amil’s professional competency standards, including the fields of accounting and management, and provide Amil professional certification as well as establish Amil Professional Associations.